Beethoven monument in Vienna: Allegory of five Beethoven symphonies - Zumbusch, Kaspar Clemens Eduard, Ritter von, 1830-1915 (sculptor):::Creator::::::::::::; Unknown (photographer):::Contributor:::::::::::: (Vienna; Austria; Gesellschaft für vervielf. Kunst)
Engraving of the allegory of five Beethoven symphonies on the Zumbusch Beethoven monument in Vienna